Biodiversity in coffee plantations of Rincón de Mora, San Ramón, Alajuela, Costa Rica - Sánchez Brenes, Rónald (2018)
The present investigation was developed in the community of Rincón de Mora, San Ramón, Alajuela, Costa Rica. The study site was eight coffee plantations of 0-5 ha that are located between 1100-1500 m.a.s.l, have a temperature of 21°C and a rainfall of 2.250 mm per year on average. The objective of this study was to assess the environmental dimension from the biodiversity issue. It was evaluated in coffee farms through five sustainability indicators, taken from the FAO SAFA tool. It is important that all the plantations obtained 100% in the indicators called change in land cover and structural diversity of ecosystems, while the other indicators had diverse results